MSCT coronary angiography in non-invasive assessment of coronary artery bypass grafts patency - Patel, Dinesh L.; Rana, Yashpal R.; Sheth, Megha M.; Patel, Samir G.; Garachh, Milin N. (International Journal of Research in Medical Sciences, 2019)
Background: Coronary artery disease (CAD) is one of the leading cause of the morbidity and mortality in India and worldwide and last decade has seen a steep rise in incidence of CAD in India and its treatment as bypass surgery. Direct visualization of the grafts and native coronary arteries by invasive catheterization is now being replaced by non-invasive CT coronary angiography with higher slice machines and newer technology as it has good temporal resolution, high scanning speed as well as low radiation dose. We share our experience of graft imaging on 128 slice CT machine. Methods: This is a retrospective, single-center, observational study. We included 500 symptomatic patients who have undergone CT study between the year 2014 to 2018 post bypass surgery. Results: Arterial grafts have a better patency rate than venous grafts. (88% vs. 64.1%). Amongst the individual arterial grafts RIMA had the best patency rate (100%) followed by LIMA (90.8%), RA (68.7%). LAD was the most commonly involved artery (91%). Conclusions: Significant absolute concordance between CT and catheter angiographic findings have been documented for all arterial and venous grafts patency in the literature. The MSCT with retrospective gating permits an accurate and non-invasive evaluation of patent and diseased arterial and vein grafts and could replace conventional angiography for the follow-up of symptomatic, stable patients. Moreover, an optimal diagnostic accuracy was also documented in the appraisal of native vessels distal to the graft anastomoses.